Essential role of RelA Ser311 phosphorylation by ζPKC in NF-κB transcriptional activation - Duran, Angeles (Oxford University Press, 2003)
The activation of the transcription factor NF-κB is central to the control of the cellular response triggered by many stimuli. Once released from the inhibitory molecule IκB, NF-κB is translocated to the nucleus, and it has to be phosphorylated to activate transcription. In ζ protein kinase C (PKC)-deficient cells, NF-κB is transcriptionally inactive and the phosphorylation of the RelA subunit in response to tumor necrosis factor (TNF-α) is severely impaired. In vitro assays showed that ζPKC directly phosphorylates RelA. Here we demonstrate that Ser311 accounts for ζPKC phosphorylation of RelA and that this site is phosphorylated in vivo in response to TNF-α. Also, an inactivating mutation of that residue severely impairs RelA transcriptional activity, blocks its anti-apoptotic function and abrogates the interaction of RelA with the co-activator CBP as well as its recruitment, and that of RNA polymerase II (Pol II) with the interleukin-6 (IL-6) promoter. The interaction of endogenous CBP with endogenous RelA is inhibited in ζPKC–/– cells, as well as the binding of Pol II to the IL-6 promoter. These results demonstrate the mechanism whereby ζPKC regulates NF-κB activation in vivo.